Experiment research on thermal mixing in horizontal T-junction: In-pipe temperature and flow characteristic research. (April 2017) - Ren, Wuyue; Yu, Guojun; Bian, Jiawei; Liu, Wang; Tian, Wenxi; Su, G.H.; Qiu, S.Z.; Wu, Qiao
Abstract: This experimental study was aimed at turbulence researches in ECC T-junction structure and it was conducted on ECC condensation heat transfer in a horizontal T-junction pipe. By using sub-cooled water in different flow rates, various flow patterns had a comparison with saturate steam in the cold leg. In the researches, the first part is dedicated to obtain the effects of hydraulic jump and back flow on T-junction thermal mixing. This research, which was based on momentum method, tries to find the influence of different flow patterns on the temperature distribution and capture the flow patterns' picture as reference. The equations, which can be employed to analyze temperature change, have been deduced after the research. And the second part of the researches focused on two-phase flow status after SI coolant mixed. The conclusion was deduced according to the pure steam SI injected condition. With some reasonable assumptions, the analysis included both steam Reynolds number and liquid Reynolds number correlations. The length of downstream is longer than that of the scaled-down distance from SI line to downcomer in PWR. And this could contribute to PWR safety analysis and find the relation between the flow status and mixed length. In addition, the test also figured out the relative velocity changes in T-junction thermal mixing following the Reynolds number research on mixed two-phase flow. This correlation could contribute to structure design improvement in PWR and prevent excessive steam from rushing to downcomer. All equations and correlations show good agreement within experiment data. Highlights: ECC condensation research based on China PWR-CPR1000. The correlation of condensation based on XJTU-ECC test was proposed. A new analysis method was proposed by using two phase flow momentum ratio number. The test report a correlation on steam and liquid Reynolds number distributions during the mixing process.